Immune Checkpoint Inhibition: Therapeutic Implications in Epithelial Ovarian Cancer - C. Longoria, Teresa; N. Eskander, Ramez (Recent Patents on Anti-Cancer Drug Discovery, 2015)
Ovarian cancer accounts for more deaths than any other gynecologic malignancy. According to the Ovarian Cancer National Alliance, overall mortality rates due to ovarian cancer have not significantly improved in 40 years, a statistic that highlights the need for innovative treatment strategies. Immune checkpoint inhibitors are part of an emerging immunotherapeutic model that seeks to “inhibit the inhibitors” of adequate cancer immunosurveillance. Immune checkpoints encompass a variety of inhibitory pathways that downregulate an immune response, which allows them to assume an important physiologic role in maintaining homeostasis. While cancer cells are adept at utilizing these pathways to their advantage, basic scientists, translational researchers, and clinical trialists are making great strides in this area of investigation. This review article will focus on the development of anti-CTLA-4 and anti-PD1 monoclonal antibodies, their current role in the treatment of advanced stage EOC, and recently published patents that incorporate the use of immune checkpoint inhibition in the treatment of cancer.
Keywords: ovarian cancer